Creating Collaborative Platform for Knowledge Transfer Based on Actor-Network Theory - Amal, Ibrahim (2009)
Knowledge management is a growth disciplines and has been widely used in organization to improve the effectiveness of the knowledge among the employee. The introduction of this concept has started in the midst of 50s where the concept of knowledge has been studied and has been enhanced to the new disciplines which are knowledge transfer and collaboration. Knowledge collaboration has been implemented creates the knowledge sharing and individual knowledge, talents and information can be effectively used. Knowledge collaboration is all about relation and connection of involved actor and this cannot be separated. This relationship is translated through an Actor-Network Theory, which is a sociology theory. This project is to study how sociology theory can be used as an interpreting and solution tool in information system field such as creating a collaborative web platform for IT Personnel in Polytechnic Malaysia. This project also shows how Actor-Network Theory can be related to system development activities such as identifying list of requirements, analyzing current system and identifying the actor’s roles. Once the actors, roles and the list of requirements have been identified, the ANT Framework for collaborative web platform has been built to represent the actor’s structure that relate. Actor-Network Diagram has been built to show the relationship among the actors. Lately, many researches has used this theory to produce and solve the problem. In briefly, the research has showed the implementation of sociology theory in information system and technology field.